Pellet stability test and feeding response of Orochromis sp. (Linnaeus, 1785) juveniles - Muhammad Hilmy Abdul Jamil (Terengganu: Universiti Malaysia Terengganu, 2013)
Pellet stability need to be highlighted in feed formulation as stable pellet ensure maximum feed utilization that necessary for growth o f the cultured fish and also reduced waste in tank that can deteriorate water quality.